Implementation of CVD Diamond Growth Methods for Selective and Efficient Formation of Color-Centers in Diamond. Issue 1728 (16th March 2015) - Gay, Stefano; Reina, Giacomo; Cianchetta, Ilaria; Tamburri, Emanuela; Angjellari, Mariglen; Terranova, Maria Letizia; Orlanducci, Silvia
ABSTRACT: We report here on the chemical methodologies that are being settled in our labs for the insertion in diamond of foreign atoms and consequent creation of fluorescent defects. The inclusion of Si, Cr, Ge, able to produce color centers, is directly obtained during the process of diamond synthesis by means of a CVD technique. The deposition of the diamond films takes place on substrates of different nature, treated following procedures specifically settled to control the insertion of the different species. The photoluminescence emission from a series of diamond samples grown on different substrates (Si, Ge and Ti) has been investigated and is discussed with reference to the morphological/structural features of the diamond phase and to the experimental procedures adopted for substrate preparation.